2020
DOI: 10.14202/vetworld.2020.963-966
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-lipoic acid ameliorates sodium valproate-induced liver injury in mice

Abstract: Aim: This study examines the effect of alpha-lipoic acid (ALA) on sodium valproate-induced liver injury through histological features of mice liver tissue. Materials and Methods: Mice were divided into three groups; (1) vehicle group, (2) sodium valproate group, and (3) sodium valproate-ALA group. The vehicle group was injected with saline intraperitoneal (i.p.) for 28 days. The sodium valproate group was injected with sodium valproate 300 mg/kg, i.p. daily for 2 weeks, after which the vehicle was adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In experimental studies, SV has been reported to elevate liver marker enzymes in serum and induce oxidative stress mediated liver injury in rats 10,11 . Therefore, SV has been used as a hepatotoxic model to evaluate the hepatoprotective efficacy of several antioxidants such as ellagic acid, 10 curcumin, N ‐acetylcysteine, 12 melatonin, 13 ginsenoside compound K 14 and alpha‐lipoic acid 15 and showed promising results. These studies have shown that antioxidants could regress the oxidative stress inducing potential of SV in experimental animals.…”
Section: Introductionmentioning
confidence: 99%
“…In experimental studies, SV has been reported to elevate liver marker enzymes in serum and induce oxidative stress mediated liver injury in rats 10,11 . Therefore, SV has been used as a hepatotoxic model to evaluate the hepatoprotective efficacy of several antioxidants such as ellagic acid, 10 curcumin, N ‐acetylcysteine, 12 melatonin, 13 ginsenoside compound K 14 and alpha‐lipoic acid 15 and showed promising results. These studies have shown that antioxidants could regress the oxidative stress inducing potential of SV in experimental animals.…”
Section: Introductionmentioning
confidence: 99%
“…Epilepsy is one of the most common neurological disorders worldwide, and approximately 90% of patients with epilepsy live in developing regions [25]. Antiepileptic drugs (AEDs) used in the treatment of epilepsy are widely used by patients [26].…”
Section: Discussionmentioning
confidence: 99%
“…VPA is an AED used to treat various seizure disorders. However, serious side effects such as hepatotoxicity, pancreatitis, thrombocytopenia, and platelet aggregation are associated with VPA treatment [25]. After treatment with VPA, changes may occur in the number and characteristics of T lymphocytes in the spleen, a central organ of the immune system [28].…”
Section: Discussionmentioning
confidence: 99%
“…Common adverse reactions include diarrhea, dyspepsia, nausea, vomiting, gastrointestinal spasm and menstrual cycle changes. Long-term use may cause pancreatitis and acute liver necrosis [47]. Its mechanism has not been fully clarified.…”
Section: Detection Of the Antiepileptic Drugs By The Ag 25 -C-fiber S...mentioning
confidence: 99%